2021
DOI: 10.1111/apps.12294
|View full text |Cite
|
Sign up to set email alerts
|

Panacea or Mixed Blessing? Learning Goal Orientation Reduces Psychological Detachment via Problem‐Solving Rumination

Abstract: This study seeks to test whether employee learning goal orientation, due to its prompting of work goal‐related thoughts at home (problem‐solving rumination), is associated with lower detachment from work during non‐work time (and higher work creativity). For learning goal‐oriented employees, the goal to achieve work‐related improvements is chronically cognitively accessible. Moreover, highly accessible work goals could become more frequently activated at home when cues about work tasks permeate the boundaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Interestingly, of the 25 studies revised, only seven studies used the complete WRRS and those included the original study in which the WRRS was developed ( Cropley et al, 2012 ; Querstret and Cropley, 2012 ; Vandevala et al, 2017 ; Dunn and Sensky, 2018 ; Sulak Akyüz and Sulak, 2019 ; Weigelt et al, 2019a ; Mullen et al, 2020 ), 11 used the affective and problem-solving pondering subscales ( Bisht, 2017 ; Kinnunen et al, 2017 , 2019 ; Querstret et al, 2017 ; Syrek et al, 2017 ; Vahle-Hinz et al, 2017 ; Firoozabadi et al, 2018a , b ; Junker et al, 2020 ; Zhang et al, 2020 ; Pauli and Lang, 2021 ), two studies used the problem-solving pondering and Detachment subscales ( Zoupanou et al, 2013 ; Mehmood and Hamstra, 2021 ), only one used the Detachment subscale ( Svetieva et al, 2017 ), and four studies used the affective rumination subscale ( Querstret et al, 2016 ; Van Laethem et al, 2019 ; Weigelt et al, 2019b ; Cropley and Collis, 2020 ; Smyth et al, 2020 ). Thus, the use of the subscales of the WRRS vary according to the researchers need and purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, of the 25 studies revised, only seven studies used the complete WRRS and those included the original study in which the WRRS was developed ( Cropley et al, 2012 ; Querstret and Cropley, 2012 ; Vandevala et al, 2017 ; Dunn and Sensky, 2018 ; Sulak Akyüz and Sulak, 2019 ; Weigelt et al, 2019a ; Mullen et al, 2020 ), 11 used the affective and problem-solving pondering subscales ( Bisht, 2017 ; Kinnunen et al, 2017 , 2019 ; Querstret et al, 2017 ; Syrek et al, 2017 ; Vahle-Hinz et al, 2017 ; Firoozabadi et al, 2018a , b ; Junker et al, 2020 ; Zhang et al, 2020 ; Pauli and Lang, 2021 ), two studies used the problem-solving pondering and Detachment subscales ( Zoupanou et al, 2013 ; Mehmood and Hamstra, 2021 ), only one used the Detachment subscale ( Svetieva et al, 2017 ), and four studies used the affective rumination subscale ( Querstret et al, 2016 ; Van Laethem et al, 2019 ; Weigelt et al, 2019b ; Cropley and Collis, 2020 ; Smyth et al, 2020 ). Thus, the use of the subscales of the WRRS vary according to the researchers need and purpose.…”
Section: Introductionmentioning
confidence: 99%
“…This line of research has demonstrated that relatively stable characteristics of the person can affect detachment from work. Studies have examined a wide variety of individual characteristics including self-evaluations (e.g., Bipp et al, 2019), personality (Sonnentag & Fritz, 2007), coping and emotion regulation (e.g., Sonnentag & Fritz, 2007), learning goal orientation (Mehmood & Hamstra, 2021), regulatory focus (Hauser et al, 2018), and perfectionism (Gluschkoff et al, 2017). The most studied predictors in this category were work-to-home segmentation preferences and heavy work investment .…”
Section: Review Of Research On Antecedents Of Psychological Detachmen...mentioning
confidence: 99%
“…We asked participants to report their experiences of rumination over breached ideology in the past few weeks by using a well-established eight-item scale (McCullough et al, 2007). Previous research has used a similar time-lag approach to measuring rumination (Calderwood et al, 2018;Deng et al, 2021;Mehmood & Hamstra, 2021). Sample items include:…”
Section: Rumination Over the Breached Ideologymentioning
confidence: 99%